2000
DOI: 10.3171/jns.2000.92.2.0284
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transluminal angioplasty for the management of symptomatic cerebral vasospasm following aneurysmal subarachnoid hemorrhage

Abstract: Transluminal cerebral angioplasty is very effective in reversing angiographically confirmed vasospasm, and anecdotal reports of its clinical utility are numerous. However, in this report the authors conclude that its superiority to medical management for symptomatic cerebral vasospasm is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(63 citation statements)
references
References 30 publications
0
58
0
5
Order By: Relevance
“…However, a recent large randomized trial investigating the effect of prophylactic endovascular treatment showed a nonsignificant reduction of DCI without a beneficial effect on outcome (Zwienenberg- Lee et al, 2008). Thus, although transluminal angioplasty and intraarterial drug administration reduce vasospasm, improvement in clinical outcome is less obvious (Polin et al, 2000). Some patients show direct clinical improvement after angioplasty, but this effect is often not sustained.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent large randomized trial investigating the effect of prophylactic endovascular treatment showed a nonsignificant reduction of DCI without a beneficial effect on outcome (Zwienenberg- Lee et al, 2008). Thus, although transluminal angioplasty and intraarterial drug administration reduce vasospasm, improvement in clinical outcome is less obvious (Polin et al, 2000). Some patients show direct clinical improvement after angioplasty, but this effect is often not sustained.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it demands an experienced endovascular surgeon and is associated with significant risk. 19,20 Intraarterial papaverine has been shown to reverse angiographic vasospasm and to reduce the velocities as detected by transcranial Doppler (TCD). 17,21 However, clinical trials have failed to demonstrate the effectiveness of intra-arterial papaverine on outcome.…”
mentioning
confidence: 99%
“…Nonetheless, there was no definite connection with angiographic alleviation and functional improvement (Laskowitz & Kolls, 2010). Moreover, radiographic vasospasm improvement lacks evidence to declare its neural functional amelioration in CV (Polin et al., 2000). It should be pointed out that EBI may be the primary cause of mortality in SAH patients (Cahill & Zhang, 2009).…”
Section: Discussionmentioning
confidence: 99%